Boundary processes and neodymium cycling along the Pacific margin of West Antarctica. (15th June 2022) - Wang, Ruixue; Williams, Thomas J.; Hillenbrand, Claus-Dieter; Ehrmann, Werner; Larkin, Christina S.; Hutchings, Alec M.; Piotrowski, Alexander M.
Abstract: Neodymium (Nd) isotopes have been utilized as a tracer of water mass source in the modern ocean and in palaeoceanographic studies, though the oceanic cycling of Nd is not yet fully constrained. Recent studies have highlighted the importance of processes that occur near the seawater – sediment interface in altering the Nd isotopic composition of bottom waters. The two major observed processes "boundary exchange" and "benthic flux" have been suggested as playing an important role in setting water mass compositions, however, more studies are needed to constrain their chemical mechanism and the extent to which these processes set the composition of deep waters. The Antarctic continental margin is an important place to study these processes because Antarctic-sourced waters dominate the Southern Ocean and ventilate the global deep ocean. This study is the first to measure and compare seawater, porewater and sediment data from along the margin of Antarctica to examine the nature of potential boundary processes. We show that a process similar to boundary exchange seems to be occurring within porewaters, modifying porewater chemistry by shifting its Nd isotopic ratios to more radiogenic values without significantly increasing the concentration of dissolved Nd. We hypothesize that this shift results from partial dissolution of radiogenic detrital particles, such as smectite, amphibole and/or volcanic glass, while re-scavenging maintains low Nd concentrations. We infer the existence of benthic flux of porewaters to deep waters by examining chemical gradients in porewaters and show that it is much lower on the Antarctic margin compared to other studies. Benthic flux appears to be slightly higher along the Antarctic Peninsula than in the Bellingshausen Sea due to partial degradation of organic matter and associated dissolution of Fe-Mn oxyhydroxides. Taken together, boundary processes do not significantly change the Nd isotopic composition of Antarctic margin seawater because while the porewaters have an altered Nd isotopic composition the Nd concentration of these porewaters is low compared to other settings.